A minority game with expected returns for modeling stock correlations. (3rd August 2018) - Yang, M.-Y.; Li, S.-P.; Zhong, L.-X.; Ren, F.
Abstract: Financial systems are complex systems which have been widely studied in recent years. We here propose a model to study stock correlations in financial markets, in which an agent's expected return for one stock is influenced by the historical return of the other stock. Each agent makes a decision based on his expected return with reference to information dissemination and the historical return of the stock. We find that the returns of the stocks are positively (negatively) correlated when agents' expected returns for one stock are positively (negatively) correlated with the historical return of the other. We provide both numerical and analytical studies and give explanations to stock correlations for cases with agents having either homogeneous or heterogeneous expected returns. The result still holds when other factors such as holding decisions and external events are included which broadens the practicability of the model.